DARK VISIONS: CINEMATIC TECHNIQUES IN MODERN NEO-NOIR FILMS - Franklin, James Alexander; Thompson, Elizabeth Marie (Ayden Journal of Management and Social Sciences, 2024)
In his seminal contribution to Ursini and Silver's 1996 Film Noir Reader, Erickson embarked on a journey to elucidate the intricacies of "neonoir" cinema, exploring its nuances from three distinct perspectives. This essay, in alignment with Erickson's exploration, delves into the core of one of these perspectives: the technical advancements facilitated by color film stock. Focused on the evolution of cinematography, this study aims to dissect the transformative technical changes that accompanied the emergence of "neo-noir." The concept of "neonoir" represents a critical juncture in cinematic history, marked by a departure from the traditional film noir aesthetic. Erickson's examination of this phenomenon in relation to technical innovations, particularly the utilization of color film stock, serves as a springboard for this analysis. The study seeks to unravel the profound impact of these advancements on the visual language of neo-noir cinema, shedding light on how technical evolution played a pivotal role in shaping the aesthetic and thematic dimensions of this cinematic genre. As the essay navigates through the intricate web of technical changes, it traces the birth of "neo-noir" alongside the evolution of cinematography. The exploration extends beyond the theoretical framework, aiming to illustrate the practical implications of these technical advancements in the visual storytelling process. By dissecting the nuances of color film stock utilization, the study aims to discern the subtle and overt shifts in cinematographic practices that defined the neo-noir landscape. The interplay between technological progress and cinematic artistry unfolds as a central theme, unraveling the symbiotic relationship between the technical and narrative facets of neo-noir cinema. Through this investigation, the essay contributes to a comprehensive understanding of the dynamic interplay between technological innovation and cinematic evolution, casting a spotlight on the birth of "neo-noir" as a transformative chapter in film history.